The impact of war and its adverse effects on women's health: A media approach to the mental and emotional health of female - Arasteh , Jamshid; Saniee, Mandana; Mirzakhanian , Ani; Mirtorabi , Hedyeh Sadat (Social Determinants of Health, 2024)
The modern world and the world of technology claim order and regularity in several aspects of life. However, the disruption of the balance in the global power structure, the existing disorder, and the ringing of the bell of war by the violent people make the daily life of human societies a system of disorder and chaos. The media plays an effective and significant role both in formulating and developing women's legal literature in international relations and global communications and the development of the women’s health system. This study has criticized the performance of the media from the viewpoint of providing the right to women's health by analyzing and describing the news published about women in the recent wars. The evidence suggests that female combatants experience war in the same way as male ones, but the experience after the war has not been pleasant for them and has brought many psychological consequences for them, and their emotional health has been affected. The media's approach to the role, position, and contribution of women during the recent war indicates the impact of the power institution and authoritarian structures, which is necessary for the media, health, and legal system of the country, to develop a legal-media system for empowering female combatants and not limiting their right to health in times of war and peace considering the ethnic, cultural, religious commonalities.